2018
DOI: 10.1073/pnas.1801693115
|View full text |Cite
|
Sign up to set email alerts
|

DEC2 modulates orexin expression and regulates sleep

Abstract: Adequate sleep is essential for physical and mental health. We previously identified a missense mutation in the human gene () leading to the familial natural short sleep behavioral trait. DEC2 is a transcription factor regulating the circadian clock in mammals, although its role in sleep regulation has been unclear. Here we report that , also known as (), gene expression is increased in the mouse model expressing the mutant h transgene (h). encodes a precursor protein of a neuropeptide producing orexin A and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
2
52
0
1
Order By: Relevance
“…This suggests that the mutant sleep phenotype involves clock gene function outside of their central time-keeping role. Interestingly mutations in some of the circadian transcription factors we identified, Per3 and Dec2, indeed lead to deficits in sleep regulation (Archer et al, 2018;He et al, 2009;Hirano et al, 2018). Our results support a role of clock genes in influencing sleep outside of their roles in generating circadian rhythms (Franken, 2013).…”
Section: Wild Type Shank3supporting
confidence: 69%
“…This suggests that the mutant sleep phenotype involves clock gene function outside of their central time-keeping role. Interestingly mutations in some of the circadian transcription factors we identified, Per3 and Dec2, indeed lead to deficits in sleep regulation (Archer et al, 2018;He et al, 2009;Hirano et al, 2018). Our results support a role of clock genes in influencing sleep outside of their roles in generating circadian rhythms (Franken, 2013).…”
Section: Wild Type Shank3supporting
confidence: 69%
“…More recent studies on the physiology of orexins have indeed shown a tight interaction between sleep‐wake state and feeding behaviour. Studies by Hirano et al reported that Basic helix‐loop‐helix family, member e41 (BHLHE41, DEC2) regulates sleep‐wake state via orexin. DEC2 is highly expressed by neurons of the suprachiasmatic nucleus of the hypothalamus, the brain region responsible for circadian clock.…”
Section: Interaction Between Eating Behaviour and Sleepmentioning
confidence: 99%
“…The total protein extraction was performed using a lysis buffer (Pierce). The total protein concentration in the extract was estimated by the Bradford method . A total of 15 μg of protein per sample were separated via 15%, 10% or 8% SDS‐PAGE, and transferred onto polyvinylidene fluoride membranes (PVDF; Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…For the former, BHLHE41 protein re‐enters the nucleus after transcription and translation and competes with CLOCK‐BMAL1 heterodimer for E‐Box element binding (through competitive inhibition). BHLHE41 functions as a suppressor of circadian rhythm regulation in this process . For non‐circadian regulation, BHLHE41 is implicated in multiple other pathways, such as BCR, notch, hypoxia, ERK/NF‐kappaB and PI3K/Akt pathways …”
Section: Introductionmentioning
confidence: 99%